Contemporary instrumental analysis / Kenneth A Rubinson, Judith F Rubinson - Rubinson, Kenneth A
Table of contents: 1. Preliminaries; 2. Statistical tests and error analysis; 3. Sampling; 4. Sample trreatments, interferences, and standards; 5. Sample size and major, minor, trace, and ultratrace components; 6. Electronics and noise; 7. Electrochemical methods; 8. Introduction to spectrometry; 9. Spectrometry for elemental analysis; 10. Infrared and Raman spectrometries: vibrational spectrometries; 11. Nuclear magnetic resonance spectrometry; 12. Mass spectrometry; 13. General introduction to separations and chromatography; 14. Liquid chromatography; 15. Gas chromatography and supercritical fluid chromatography; 16. Separations by applied voltage: electroseparations; 17. Digital signal acquisition and signal treatment; 18. Kinetic methods. Appendices. Answers. Index.